2016
DOI: 10.1007/s11060-015-2032-6
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent functional and metabolic assessment of brain tumors using hybrid PET/MR imaging

Abstract: To evaluate diagnostic accuracy of perfusion weighted imaging (PWI) and positron emission tomography (PET) using an integrated PET/MR system in tumor grading as well as in differentiating recurrent tumor from treatment-induced effects (TIE) in brain tumor patients. Twenty patients (Group A: treatment naïve, 9 patients with 16 lesions; Group B: post-therapy, 11 patients with 18 lesions) underwent fluorine 18 ((18)F) fluorodeoxyglucose (FDG) brain PET/MR with PWI. Two blinded readers predicted low versus high-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…Most other studies provided P values and reached statistical significance for the use of rCBV to distinguish true progression and treatment-related effects with sensitivities ranging from 63% [38] [39]. Among these studies however, optimum cut-off values ranged extensively from 0.71 according to Hu et al [24], to as high as 5.01 in Sacconi et al [33]. Unfortunately, the issue of wide variability in cut-off values is known to the literature because of a lack of standardisation in acquiring and processing rCBV values, including different scanner technologies, varying algorithms for processing, and at times, a lack of quantification.…”
Section: Dynamic Susceptibility Contrast (Dsc) Mrimentioning
confidence: 99%
See 1 more Smart Citation
“…Most other studies provided P values and reached statistical significance for the use of rCBV to distinguish true progression and treatment-related effects with sensitivities ranging from 63% [38] [39]. Among these studies however, optimum cut-off values ranged extensively from 0.71 according to Hu et al [24], to as high as 5.01 in Sacconi et al [33]. Unfortunately, the issue of wide variability in cut-off values is known to the literature because of a lack of standardisation in acquiring and processing rCBV values, including different scanner technologies, varying algorithms for processing, and at times, a lack of quantification.…”
Section: Dynamic Susceptibility Contrast (Dsc) Mrimentioning
confidence: 99%
“…[43], and 1 used ASL + DSC + DCE [34] adjunctive to other non-perfusion based techniques. In general, the composite measures exhibited greater diagnostic accuracy compared to single parameters, except for 3 studies which found no statistically significant difference for certain measures [19] [32] [33]. Further, studies utilising three or more parameters in a single measure had greater diagnostic accuracy when more imaging modalities were utilised compositely (see Table 4…”
Section: Arterial Spin Line Imaging (Asl)mentioning
confidence: 99%
“…As previously stated, hybrid MRI/PET has great advantages in the differential diagnosis of brain tumors, grading of gliomas, assessment of progression, and the distinction between necrosis and recurrence of tumors [162][163][164][165][166]. Additionally, it is an important tool for the selection of sites for biopsies and in the evaluation of treatment effects [160,[167][168][169][170][171][172][173][174][175][176]. Adding diffusion tensor imaging/fiber tracking, fMRI, PWI, MRS, and activation-PET to multimodal imaging can enhance the assessment of a tumor on the functional networks in the brain [177][178][179][180][181] and show anaerobic changes as well as the effect on efferent and connecting fiber tracts and on task-related activation patterns.…”
Section: The Future: Hybrid Pet/mri Systemsmentioning
confidence: 99%
“…They found differing spatial distribution between regions of elevated rCBV and increased 18 F-FDG uptake. 69 Future challenges for the PET/MR community include defining the optimal set of MR imaging parameters and standardizing their acquisition and processing for reproducibility, identifying the best PET radiotracer for each clinical question, and justifying the clinical utility of multimodal imaging.…”
Section: Applicationsmentioning
confidence: 99%